Implications of the Rohingya Relocation from Cox's Bazar to Bhasan Char, Bangladesh. Issue 4 (December 2022) - Islam, Md. Didarul; Siddika, Ayesha
This IMR Dispatch attempts to elucidate the different concerns of human right groups and international communities over the relocation of the Rohingyas, a forcefully displaced ethnic minority of Myanmar, from the Cox's Bazar refugee camps, in mainland Bangladesh, to a newly developed island, Bhasan Char, in the Bay of Bengal. Of the nearly 1 million Rohingyas currently living in Cox's Bazar camps, the Bangladesh government has started relocating 100, 000 Rohingyas to Bhasan Char. International organizations have expressed three concerns over this relocation strategy: first, that the Rohingyas have been relocated to Bhasan Char forcibly, second, that since Bhasan Char is a newly built island, there are potential environmental risks for the Rohingyas, and third, that this relocation does not ensure that the Rohingyas' human rights will be respected on the island. The Bangladesh government, however, has dismissed these allegations, arguing that the relocation of 100, 000 Rohingyas is voluntary and that the island provides them an opportunity for improved living. This IMR Dispatch reflects on those allegations concerning the relocation strategy, with the goal of drawing migration scholars' attention to these developments. Since the Rohingyas are already a forcibly displaced community, migration scholars should pay close attention to this re-migration or onward migration of large numbers of Rohingyas to a new island and its implications for host-country approaches to forced migration.